Transformation of the Role of School Superintendents in Implementation of the Independent Curriculum Case Studies (Supervisory Roles Post-Director General GTK 2023) - Mulyadi, Mulyadi; Jabar, Cepi Safruddin Abdul (Journal of Educational Sciences, 2025)
This study aims to analyze the transformation of the role of school supervisors in supporting the implementation of the Merdeka Curriculum following the issuance of the Regulation of the Director General of Teachers and Education Personnel (Perdirjen GTK) Number 4831/B/HK.03.01/2023 at public junior high schools in Wates District, Kulon Progo. The research also explores the challenges faced by supervisors after the regulation and the efforts made to overcome them. This study employed a descriptive qualitative approach, conducted through in-depth interviews, observations, and document studies involving supervisors and principals to understand their experiences and perceptions regarding the new supervisory roles. Data analysis followed the interactive model of Miles and Huberman, including data collection, condensation, display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that supervisors face several challenges, such as limited training, inadequate resources, and an imbalance between the number of supervisors and schools under supervision. Despite these constraints, supervisors have adopted collaborative and adaptive strategies to assist principals in designing more innovative and contextual learning programs. The study concludes that the transformation of the supervisory role into that of a facilitator and mentor contributes significantly to achieving more relevant and student-centered educational outcomes.